Suffering in Silence: An Analysis of Women’s Experiences in AyaanHirsi Ali’s Infidel - L, Dr. Anupama (SMART MOVES JOURNAL IJELLH, 2018)
AyaanHirsi Ali in Infidel (2006) highlights the severe oppression that women encounters in various parts of the world. She examines several ways by which women are oppressed. Forced marriages, child marriages, polygamy, female genital mutilation and the neglect that a girl child faces can all affect the sense of self in women and girl children. Women are still not permitted to enter certain fields. The male dominated society is hostile and imposes more restrictions when women try to assert their rights. Though several women in the modern era are literate and are aware of their rights they still struggle against several severe problems.Her story has a positive impact on others in similar position as it indicates how she has reached the other side after enormous toil and suffering. There are stark descriptions of evil husbands who do not regard their wives as individuals and as equal partners. The lives of women were difficult. They had to be covered, be obedient, and accept everything without arguing. Her suggestions are valuable and her arguments are persuasive as she speaks from her own experiences.